PERAN ORANG TUA PADA PENDIDIKAN SEKSUALITAS KAUM REMAJA DALAM TERANG SERUAN APOSTOLIK PASCASINODE AMORIS LAETITIA - Kurniadi, Benediktus Benteng; Siringo Ringo, Erika (STP St. Bonaventura Medan, 2022)
Sexuality education is an effort to provide education, knowledge and orientation regarding sexuality from an early age in order to prevent wrong understanding and practice, increase appropriate knowledge, strengthen moral values ​​and positive attitudes regarding sexuality. This article tries to explore the importance of the role or responsibility of parents in dealing with the urgency of the need for knowledge and correct understanding of sexuality in adolescents in the light of the church document, namely the Post-Synodal Apostolic Exhortation Amoris Laetitia. This writing uses the Library Research method by collecting materials sourced from Church documents, journals, books and scientific works related to this theme. The results of this writing confirm that the role of parents is: 1) helping self-knowledge for teenagers according to age development. Adolescents understand their identity, self-identity, needs and responsibilities regarding their role in society. 2) help self-control to help children control themselves and prevent themselves from bad information about sexuality. 3) Provide correct information so that children are able to filter information from other people, including peers and communication media. 4) Raising critical awareness helps children face sexual deviations and has a positive influence on the child's development. 5) building a sense of politeness to help children carry out norms so that they respect each other's differences